Students’ Anxiety on Their Public Speaking - Rini Kesuma Siregar (Institut Agama Islam Negeri (IAIN) Padangsidimpuan, 2019)
The purpose of this research is to find out the anxiety of students when speaking in English in front of the public in SMK Teruna Padangsidimpuan. This study used qualitative research with descriptive methods. Data is taken from questionnaires and interviews with students. The results of this study indicated that students are at medium and serious level of anxiety because each student has different abilities. This shows that when a student speaks in front of the public they still feel anxious, especially because the anxiety factor is not confident, unable speak English and rarely appear in public.